Teachers’ Perception of Project-Based Learning: Challenges and Strategies in Evaluating Student Integrated Project Result of Narrative and Procedure Text - Prastica, Aprilia Dwi Dharma; Soraya, Irma; Nafiah, Marfuatin (ICONELT, 2024)
Project-based learning (PJBL) is a learning method that provides opportunities for students to learn independently by doing group projects, which can gain the participation of the students than other traditional learning methods. This study tries to investigate teachers’ perceptions about the challenges faced and the strategies used by English teachers at MTsN 2 Sidoarjo, located in Sidoarjo, East Java, Indonesia, in evaluating the integration of two different learning topics into the same learning approach. This study uses qualitative case study research involving three English teachers as participants. The interview method was used in this study, which asked the respondents a list of questions. The findings revealed that the teachers had a positive perception of project-based learning, as it allowed students to improve their collaborative skills, exchange ideas, and tackle real-world problems. However, integrating two topics posed challenges, such as limited time and students’ difficulty understanding the project’s step-by-step process. Despite these challenges, all participants agreed that project-based learning was a valuable approach.